2021
DOI: 10.3389/fimmu.2021.793918
|View full text |Cite
|
Sign up to set email alerts
|

IL-15Rα-Independent IL-15 Signaling in Non-NK Cell-Derived IFNγ Driven Control of Listeria monocytogenes

Abstract: Interleukin-15, produced by hematopoietic and parenchymal cells, maintains immune cell homeostasis and facilitates activation of lymphoid and myeloid cell subsets. IL-15 interacts with the ligand-binding receptor chain IL-15Rα during biosynthesis, and the IL-15:IL-15Rα complex is trans-presented to responder cells that express the IL-2/15Rβγc complex to initiate signaling. IL-15-deficient and IL-15Rα-deficient mice display similar alterations in immune cell subsets. Thus, the trimeric IL-15Rαβγc complex is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Studies using Il15 −/− mice have implicated IL‐15 in immune responses against oral Salmonella infection by promoting the activity of IL‐15‐dependent NK cells (Ashkar et al, 2009). However, we have shown that while Il15 −/− mice are highly susceptible to systemic low‐dose Listeria monocytogenes infection, Il15ra −/− mice are not (Nandi et al, 2021), even though NK cells and ILC1s require both IL‐15 and IL‐15Rα for their maintenance and activation (Fuchs et al, 2013; Lodolce et al, 1998; Schluns et al, 2004). To determine whether this difference is maintained for Salmonella infections (and hence, establish base‐line Il15 −/− and Il15ra −/− mice susceptibility to Salmonella ), we infected mice orally with 5 × 10 7 cfu of the virulent Salmonella SL1344 strain.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies using Il15 −/− mice have implicated IL‐15 in immune responses against oral Salmonella infection by promoting the activity of IL‐15‐dependent NK cells (Ashkar et al, 2009). However, we have shown that while Il15 −/− mice are highly susceptible to systemic low‐dose Listeria monocytogenes infection, Il15ra −/− mice are not (Nandi et al, 2021), even though NK cells and ILC1s require both IL‐15 and IL‐15Rα for their maintenance and activation (Fuchs et al, 2013; Lodolce et al, 1998; Schluns et al, 2004). To determine whether this difference is maintained for Salmonella infections (and hence, establish base‐line Il15 −/− and Il15ra −/− mice susceptibility to Salmonella ), we infected mice orally with 5 × 10 7 cfu of the virulent Salmonella SL1344 strain.…”
Section: Resultsmentioning
confidence: 99%
“…C. rodentium colonizes the intestinal lumen without causing invasive infection. As mice without IL‐15 were more susceptible to Listeria monocytogenes (Nandi et al, 2021) and non‐virulent Salmonella (Figure 1c), as opposed to mice without IL‐15Rα, we assessed the kinetics of C. rodentium fecal load after oral infection in WT, Il15 −/− , mice and Il15ra −/− mice. On Day 14 post‐infection, irrespective of the genotype, the bacterial load was comparable (Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations